South Korean Hurry-Hurry (빨리 빨리) COVID-19 Strategy: Privacy Concern, No-Lockdown, and Discriminations - Annisa Pratamasari (Global Strategis, 2020)
South Korea has been hailed as one of the most successful countries in containing the spread of the novel coronavirus, COVID-19, within a relatively short period. Some argued that East Asian countries’ success could be attributed to Confucianist culture, to which I disagree. In this paper, I shall describe in details how Korean government managed to curb the Covid-19 spread with the combination of epidemiological investigation, advanced technology, and haste (빨리 빨리) culture, leading to a hurry-hurry strategy unique to South Korea. I would also outline some social impacts on LGBT-Q communities and the exclusion of foreign residents in South Korean pandemic efforts.Keywords: South Korea, COVID-19, hurry-hurry strategy.Korea Selatan dipuja sebagai salah satu negara tersukses dalam membendung penyebaran coronavirus, COVID-19, dalam waktu yang terbilang singkat. Beberapa tulisan berargumen bahwa kesuksesan negara-negara Asia Timur merupakan berkat nilai-nilai Konfusius mereka, yang tidak penulis setujui. Di artikel ini, penulis akan mendeskripsikan secara detail bagaimana pemerintah Korea mampu membendung penyebaran COVID-19 melalui kombinasi investigasi epidemiologis, teknologi mutakhir, dan budaya buru-buru (빨리 빨리) mereka, yang berkontribusi terhadap ‘hurry-hurry strategy’ unik milik Korea Selatan. Selain itu, penulis juga akan menjabarkan dampak sosial bagi komunitas LGBT-Q dan ekslusi penduduk asing dalam kebijakan penanggulangan pandemik di Korea Selatan.Kata-kata kunci: Korea Selatan, COVID-19, hurry-hurry strategy.